Secondary tax and its effect on the cost of capital and shareholder value of South African JSE listed companies - J. H.v.H De Wet; A. D. Das (Acta Commercii, 2008)
Background: The introduction of a secondary tax on companies (STC) and the lowering of the normal income tax rate in 1993 constituted a dramatic change in the tax structure of South African organisations. The original intention of these changes was to encourage organisations to re-invest profits to make use of capital investment opportunities. It was also anticipated that these tax changes would lower the cost of capital of organisations.